1997
DOI: 10.1377/hlthaff.16.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Will Quality Report Cards Help Consumers?

Abstract: This study assesses the relationship between the salience of quality information and how well it is understood by consumers. The analysis is based on survey data and content analysis from focus-group data (104 participants). The findings show that poorly understood indicators are viewed as not useful. Consumers often do not understand quality information because they do not understand the current health care context. All of this suggests that salience alone is not sufficient to determine which indicators shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
0
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(105 citation statements)
references
References 4 publications
4
95
0
6
Order By: Relevance
“…760 -762,766 With implementation of healthcare reform legislation that increases access of consumers and payers to objective data and more easily understood data presentations, the influence of public report cards is likely to increase in the future. 762,[767][768][769][770][771] As this occurs, it will be important to monitor unintended negative consequences, such as "gaming" of the reporting system 772 and avoidance of high-risk patients (risk aversion), the precise group of patients who are most likely to benefit from aggressive intervention. [773][774][775][776] Methodological considerations are important for provider profiling and public reporting.…”
Section: Public Reporting Of Cardiac Surgerymentioning
confidence: 99%
“…760 -762,766 With implementation of healthcare reform legislation that increases access of consumers and payers to objective data and more easily understood data presentations, the influence of public report cards is likely to increase in the future. 762,[767][768][769][770][771] As this occurs, it will be important to monitor unintended negative consequences, such as "gaming" of the reporting system 772 and avoidance of high-risk patients (risk aversion), the precise group of patients who are most likely to benefit from aggressive intervention. [773][774][775][776] Methodological considerations are important for provider profiling and public reporting.…”
Section: Public Reporting Of Cardiac Surgerymentioning
confidence: 99%
“…Hibbard & Jewett (14,15,18) published a series of papers using focus groups to identify useful indicators of quality to include in report cards. In their research (14), they studied three groups: privately insured, uninsured, and members of Oregon's Health Plan, which provides managed care to Medicaid recipients.…”
Section: Consumer Preferences For Health Plan Performance Measuresmentioning
confidence: 99%
“…These studies measured consumers' understanding of and preferences for various dimensions of health care quality and measurement approaches and are useful for predicting consumers reactions to physician-level quality measures, though to date such measures are not publicly reported on a widespread basis. Hibbard and Jewett (1997) conducted focus groups to determine why some consumers fail to use available quality information in making plan and provider choices. They found that consumers lack understanding of the organization and delivery of care in managed care settings and that consumers tend to rely on more fully understandable measures, such as interpersonal skills of providers.…”
Section: Introductionmentioning
confidence: 99%